Development of Highly Functional Biomaterials by Decoupling and Recombining Material Properties. Issue 9 (22nd December 2015) - Danoux, Charlène; Sun, Lanying; Koçer, Gülistan; Birgani, Zeinab Tahmasebi; Barata, David; Barralet, Jake; van Blitterswijk, Clemens; Truckenmüller, Roman; Habibovic, Pamela
Abstract : Development of functional biomaterials by a design‐driven approach is described, whereby individual properties are first decoupled to investigate their sole effects on a biological process. Following this investigation, they are recombined in such a way that the overall performance and applicability of the biomaterial is improved. This is in contrast to classical, processing‐driven biomaterials development where the properties of a material are mainly determined by the possibilities of the technique used to produce it.